Smart hydrogels with order-of-magnitude enhanced sensitivity for smartphone compass-based chemical sensing - Mark S. Ferris; Anthony Adesso; Gary Zabow (Sensors and Actuators Reports)
Smartphone-based platforms have the potential to provide low-cost and accessible measurement tools. A first proof-of-concept study recently introduced magnetometer-based smartphone diagnostics, which use the phone compass for signal transduction, as a complement to the numerous existing optical options, which use the phone camera. With the use of motion-amplifying bilayer hydrogel actuators to translate chemical concentrations into changes in magnetic field strengths, this new form of magnetometer-based smartphone diagnostic achieved promising sensitivity with low cost, but its ultimate sensitivity was never explored. Here, we further enhance the sensitivity of such platforms, experimentally demonstrating a quadratic dependence between bilayer length and sensitivity that yields at least an order-of-magnitude gain over the proof-of-concept to reach an estimated sensitivity of 40 µpH. The technique is demonstrated on pH hydrogel actuators, but since it requires changing only the geometry of the actuator, it can be applied universally, regardless of the target analyte. A full analytical model of sensor response is also presented, suggesting additional prospects for increasing sensitivity and control over sensor dynamic and linear ranges. Such enhancements in sensitivity expand potential applications in human health and environmental monitoring.